S80 A comparison of the clinical response to mepolizumab and benralizumab at 4 weeks. (December 2018) - Roxas, C; Fernandes, M; Green, L; d'Ancona, G; Kavanagh, J; Kent, BD; Jackson, DJ
Abstract : Background: Mepolizumab and benralizumab are biologic therapies licensed for the treatment of severe eosinophilic asthma. Mepolizumab is a serum neutralising antibody against interleukin (IL)−5 whereas benralizumab targets the IL-5 receptor. In clinical trials both therapies lead to similar reductions in exacerbation frequency. In the absence of head-to-head data we sought to compare the early clinical and inflammatory response to these treatments. Methods: A retrospective review of adult patients with severe eosinophilic asthma treated with mepolizumab and benralizumab at Guy's Severe Asthma Centre was carried out. Baseline characteristics and change from baseline at 4 weeks in blood eosinophil count, FeNO, FEV1 and ACQ6 was compared between patients treated with mepolizumab and those receiving benralizumab. Results: Seventy-six patients including 38 treated with mepolizumab (55% female, mean age 54±11) and 38 treated with benralizumab (61% female, mean age 51±12) were included in this analysis. An equal number of patients in each group (28/38) were on maintenance oral corticosteroid treatment. The baseline blood eosinophil counts, FeNO, FEV1 and ACQ6 levels were not statistically different between groups. At 4 weeks, the absolute reduction in blood eosinophil count was 297±505 cells/mcL for benralizumab vs 166±207 cells/mcL for mepolizumab. The magnitude of this reduction was not statistically different between treatments (p=0.14), however, all 38 patients treated with benralizumab had undetectable blood eosinophils at 4 weeks compared to 19/38 in the mepolizumab group (p<0.001). Levels of FeNO did not significantly change with either treatment. There was a trend towards a greater improvement in ACQ6 with benralizumab (mean baseline ACQ6: 2.67±1.42, week 4 ACQ6 1.89±1.01, change −0.78) compared to mepolizumab (baseline ACQ6: 2.57±1.05, week 4 ACQ6: 2.15±1.28, change −0.38), p=0.087. A trend towards greater improvement in FEV1 was also seen for benralizumab (baseline: 1.72±0.66L, week 4: 1.85±0.66L) compared to mepolizumab (baseline: 1.99±0.85L, week 4: 1.93±0.73), p=0.064. Conclusion: A retrospective review of patients treated with either mepolizumab or benralizumab highlights non-significant trends towards improved ACQ6 and FEV1 with benralizumab at the time of the second dose at 4 weeks. This may reflect a more potent eosinophil-depleting mechanism of action with benralizumab.